2019
DOI: 10.3389/fpsyg.2019.02491
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Consumer Behavior in the Wine Industry and Its Consequences for Wineries: A Case Study of a Spanish Company

Abstract: The widening gap between production and domestic consumption has led Spain to become the country with the largest volume of wine exports, of which it has a global market share of 20.5%. Wineries in Spain have, in recent years, undergone important transformation and modernization processes, while their customers have simultaneously acquired more power than ever before owing to both the availability of information and the technological means required to access that information. The objectives of this paper are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The findings provide empirical evidence and theoretically complement previous research. The findings of this study show that of the analyzed variables the brand performance (BP) has the strongest impact on the brand equity (brand value coefficients BP3 = 0.914), which is consistent with the conclusions [29,31,32,34,90] on the importance of the brand for increasing turnover and improving the overall business performance of wineries. The answer to market challenges is certainly communication [17][18][19][20], marketing tools [15,16], informing [27] and educating producers and consumers [21,78,148,149], as well as clear differentiation and development of loyalty [30], and image [38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings provide empirical evidence and theoretically complement previous research. The findings of this study show that of the analyzed variables the brand performance (BP) has the strongest impact on the brand equity (brand value coefficients BP3 = 0.914), which is consistent with the conclusions [29,31,32,34,90] on the importance of the brand for increasing turnover and improving the overall business performance of wineries. The answer to market challenges is certainly communication [17][18][19][20], marketing tools [15,16], informing [27] and educating producers and consumers [21,78,148,149], as well as clear differentiation and development of loyalty [30], and image [38].…”
Section: Discussionsupporting
confidence: 89%
“…Efficient marketing communication [27] leads to company profiles with a desired image and creates an appropriate position in the consciousness of consumers and the general public [28] contributing to an increased awareness on sustainability. Muñoz et al [29] pointed to the importance of the brand in the prevention of wine counterfeiting. They concluded that proactivity and differentiation of wine, the development of loyalty of wine consumers [30], the improvement and the guarantee of the wine quality, the geographical indication [31][32][33][34] contribute to the purchase and the brand recognition [35] and the overall performance of the wineries.…”
Section: Business Performance Of the Winerymentioning
confidence: 99%